PELAKSANAAN PERATURAN BUPATI NOMOR 58 TAHUN 2017 TENTANG KODE ETIK DAN KODE PERILAKU PEGAWAI NEGERI SIPIL DI LINGKUNGAN PEMERINTAH KABUPATEN BANDUNG TERHADAP PELANGGARAN NETRALITAS ASN DI PILKADA KABUPATEN BANDUNG - Rangga Julian Hadi (Khazanah Hukum, 2021)
The ASN Neutrality Violation is the highest trend in the holding of the 2020 Regional Head elections (Pilkada) with ASN conditions for the sake of maintaining and advancing the rank of ASN doing practical politics by participating in practical political activities, especially ASN Head of Rancaekek Sub-district Bandung Baban Banjar recommended by the State Civil Apparatus Commission (KASN) ) to be given moral and administrative sanctions by the Civil Service Officer (PPK), namely the Regent of Bandung as the executor and implement the Regulation of Perbup No. 58 of 2017 concerning the Code of Ethics and Code of Conduct for Civil Servants in the Bandung Regency Government in providing sanctions to ASNs who violate Neutrality during the implementation of the Pilkada in Bandung Regency